PROBLEMS INVOLVING CHILDREN WITH HEARING PROBLEMS IN INCLUSIVE EDUCATION (British Journal of Global Ecology and Sustainable Development, 2024)
This article discusses the methods of teaching children with hearing impairments in normal grades and the work being done to ensure their place in society. The effective activity of teachers, their deep and diverse professional knowledge, methods of knowledge are given.